2020
DOI: 10.1002/ajoc.201900709
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Sitagliptin

Abstract: A highly enantioselective synthesis of sitagliptin, a potent DPP‐4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We then tested L1 in Ru-catalyzed asymmetric hydrogenations of unprotected enamine 11. To our delight, L1 also worked quite well, providing the enantiomer of an antidiabetic drug (+)-sitagliptin 22 on the gram scale, with 83% yield, and an almost enantiomerically pure form (>99% ee), which is comparable with the Ru/DM-SegPhos catalytic system. 23 Furthermore, by using L1, (S,S)-DPEN, and (R,R)-DPEN, we prepared two diphosphine/diamine-Ru complexes RuCl 2 (L1)[(S,S)-DPEN] and RuCl 2 (L1)[(R,R)-DPEN] (Scheme 3).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…We then tested L1 in Ru-catalyzed asymmetric hydrogenations of unprotected enamine 11. To our delight, L1 also worked quite well, providing the enantiomer of an antidiabetic drug (+)-sitagliptin 22 on the gram scale, with 83% yield, and an almost enantiomerically pure form (>99% ee), which is comparable with the Ru/DM-SegPhos catalytic system. 23 Furthermore, by using L1, (S,S)-DPEN, and (R,R)-DPEN, we prepared two diphosphine/diamine-Ru complexes RuCl 2 (L1)[(S,S)-DPEN] and RuCl 2 (L1)[(R,R)-DPEN] (Scheme 3).…”
mentioning
confidence: 87%
“…We then tested L1 in Ru-catalyzed asymmetric hydrogenations of unprotected enamine 11 . To our delight, L1 also worked quite well, providing the enantiomer of an antidiabetic drug (+)-sitagliptin on the gram scale, with 83% yield, and an almost enantiomerically pure form (>99% ee), which is comparable with the Ru/DM-SegPhos catalytic system …”
mentioning
confidence: 98%
“…More recently, Chikkali and co-workers reported that Rh complexes bearing chiral FerroLANE ligands also catalyze the AH of S110 to yield sitagliptin with excellent enantioselectivity (98% ee). 406 The asymmetric synthesis of P110 was also accomplished via direct asymmetric reductive amination (ARA) with unprecedented levels of asymmetric induction. 407 In addition, Ru catalysis has been successfully applied in both ARA or direct AH of unprotected enamines for the preparation of other pharmacologically relevant compounds.…”
Section: Unprotected Enaminesmentioning
confidence: 99%
“…P110 was obtained in 98% yield and 95% ee (improved to >99% ee by recrystallization) using (R C ,R p ) -L21a . More recently, Chikkali and co-workers reported that Rh complexes bearing chiral FerroLANE ligands also catalyze the AH of S110 to yield sitagliptin with excellent enantioselectivity (98% ee) . The asymmetric synthesis of P110 was also accomplished via direct asymmetric reductive amination (ARA) with unprecedented levels of asymmetric induction .…”
Section: Asymmetric Hydrogenation Of Enaminesmentioning
confidence: 99%
“…The transition metal‐catalyzed asymmetric hydrogenation of alkenes using chiral ligand is an essential tool to obtain chiral pharmaceuticals [21] . The conventional AH model utilizes either monodentate ligands that suffer from limited selectivity or bidentate ligands which are more selective but less reactive and require tedious synthesis [22,23] .…”
Section: Introductionmentioning
confidence: 99%